The History and Development of Tafsir Thought in Indonesia: Reformist-Modernist Islamic Ideology in Exegesis - Muhamad Aidul Mubarak Mubarak; Fikri Fillaili; R. Muhammad Farhal Azkiya; Yogi Muldani Hendrawan (Tunas Harapan Ummat Foundation, 2024)
This paper examines the development of Qur'anic exegesis in Indonesia within the context of Islamic reform movements originating from the Middle East, particularly during the early 20th century reformist-modernist era. Through historical-philosophical analysis, this research traces the intellectual networks between Indonesia and Islamic scholarly centers in the Middle East, especially Haramayn and Egypt. The main focus is on the transmission of Muhammad Abduh's thought and its influence on Qur'anic interpretation in Indonesia. This study reveals the dynamics of acceptance of reform ideas among Indonesian Muslims, as well as the contributions of local reformist-modernist figures in developing a more contextual and rational methodology of tafsir. The analysis also includes the evolution of tafsir thought from the classical era to modernity, considering the socio-historical factors that influenced this development. The research findings show significant transformations in the approach to Qur'anic interpretation in Indonesia, reflecting a synthesis between the classical Islamic intellectual tradition and the demands of modernity. This research contributes to a more comprehensive understanding of the dynamics of Islamic thought in Indonesia and its position in the global Islamic intellectual landscape.